Seroprevalence and associated risk factors of peste des petits ruminants in sheep and goats in three districts of the Central Oromia Region, Ethiopia - Wendimu, Tilahun Guday; Dinbiso, Tegegn Dilbato; Lobago, Demeke Sibhatu; Marami, Lencho Megersa (Frontiers in Veterinary Science, 2024)
BackgroundPeste des petits ruminants (PPR) is a viral disease that affects domestic and wild small ruminants and camels in Africa, the Middle East, and Asia. Following the successful eradication of rinderpest, the World Organization for Animal Health (WOAH) and the Food and Agriculture Organization (FAO) have undertaken to eradicate PPR by 2030. Regular surveillance and monitoring of the disease in various regions of Ethiopia are crucial to achieving this goal. This study aimed to estimate the prevalence of PPR, assess community awareness of PPR infection, and examine the associated risk factors of the disease in selected districts of the Central Oromia Region, Ethiopia.MethodThe study collected 384 serum samples from 73 flocks containing 217 sheep and 167 goats using a multi-stage sampling technique. A competitive enzyme-linked immunosorbent assay (c-ELISA) was used to detect antibodies against the PPR virus. Additionally, a pre-tested questionnaire was used to gather information on community awareness and potential risk factors for PPRV infection in the study area.ResultsThe study found that the overall prevalence of PPR in flocks was 71.2% [95% confidence interval (CI): 59.4%−81.2%]. The prevalence of PPR at the animal level was 50% (95% CI: 44.9%−55.1%), with sheep having a prevalence of 54.4% (95% CI: 47.0%−60.6%) and goats having a prevalence of 44.3% (95% CI: 36.6%−52.2%). The study also found that districts, flock size, and agroecology were independent predictors of PPRV seropositivity in sheep, whereas districts, origin, and mixed species were independent predictors of PPRV seropositivity in goats.ConclusionThe study revealed a high prevalence of PPR in sheep and goats in the study area. To prevent the spread of the disease, the study suggests quarantining animals before introducing them to districts, regular PPR vaccination, and isolation and molecular characterization of the PPR virus circulating in the study area.